FinTech-Enabled Green Bonds for Carbon Emission Reduction in Developing Economies: A Systematic Review of Economic and Policy Implications - Alfalah, Banan; Zughoul , Omar; Momani , Fayiz (International Journal of Energy Economics and Policy, 2025)
This systematic review investigates the intersection of FinTech innovation and green bond deployment in addressing carbon emissions and promoting sustainable finance in developing economies. Drawing from 100 peer-reviewed studies sourced from Scopus, Web of Science, and Springer, the review synthesizes findings across five thematic domains: (1) digital finance infrastructure supporting green bond issuance, (2) environmental outcomes linked to green bond-funded projects, (3) policy and regulatory frameworks enabling FinTech and green finance alignment, (4) financial market dynamics and investor behavior in emerging economies, and (5) socioeconomic impacts of FinTech-enabled green bond financing. The findings suggest that FinTech tools—such as blockchain, AI, and digital ID systems—play a pivotal role in enhancing transparency, investor trust, and accessibility of green bonds. Additionally, green bond markets that integrate FinTech solutions demonstrate improved carbon performance metrics, more inclusive financial access, and better regulatory compliance. However, gaps persist in policy harmonization, scalability in low-income regions, and empirical assessment of long-term social outcomes. The review concludes by outlining practical recommendations for policymakers and financial institutions, while identifying key areas for future research, including causality testing, governance of digital platforms, and cross-border regulatory alignment.